Needs Assessment in Curriculum Development for Madrasah Ibtidaiyah Teacher Education Study Program at IAIN Palangka Raya - Rizal, Setria Utama; Hikmah, Nurul (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
The Madrasah Ibtidaiyah Teacher Education (PGMI) Study Program at IAIN Palangka Raya is the only PGMI study program in Central Kalimantan Province. To meet the needs of MI teachers in the province of Central Kalimantan, the PGMI study program must continue to develop a curriculum that meets the needs of stakeholders. The purpose of this study was to describe whether the need assessment carried out in the curriculum development of the PGMI study program IAIN Palangka Raya was in accordance with the needs of stakeholders. This research method used descriptive-qualitative. Data collection techniques used interviews, observation, and documentation with the subject of the secretary of the Madrasah Ibtidaiyah teacher education study program and stakeholders (five madrasah/school principals and five civil servant teachers) at MIN 1, 2, 3, MIS Miftahul Huda 2 and SDN 5 Menteng, Palangka Raya City. The results showed that the development of the curriculum for the primary school teacher education study program at IAIN Palangka Raya was based on MBKM and OBE with several changes and additions to courses: adding the credit load for general courses and reducing the credit load for religious courses, streamlining the credit load for religious courses to become PAI courses, adding the Merdeka Learning Merdeka Campus program, namely Teaching Assistance in 2022 and adding a lecturer exchange program. Curriculum development was carried out by conducting a need assessment involving stakeholders, graduate users, students, deputy dean I and homebase lecturers with study program expertise.